Observational suspected adverse drug reaction profiles of fluoro-pharmaceuticals and potential mimicry of per- and polyfluoroalkyl substances (PFAS) in the United Kingdom - Banurja Balasubramaniam; Alan M. Jones (PLoS ONE, 2025)
Aims The aim of this research is to explore the suspected adverse drug reactions (ADRs) of perfluorinated medicines to determine whether side effects commonly associated with per- and poly-fluoroalkyl substances (PFAS) exposure were correlated to the type or number of fluorine atoms in these medications. Methods Thirteen fluorinated drugs and six non-fluorinated (or low fluorinated) comparators were selected after systematic triage. The reported ADR data from the Medicines and Healthcare Products Regulatory Agency’s (MHRA) Yellow Card, and prescribing data from the OpenPrescribing database and the National Health Service Business Service Authority (NHSBSA) over a 5-year period were curated. Prescribing data was used to standardise the ADRs by calculating ADRs/1,000,000 items dispensed for selected system organ classes (SOCs), associated with PFAS exposure, for all 19 drugs. The physiochemical and pharmacological properties of the selected drugs were determined from ChemDraw version 23.1.1, Drug Bank, electronic medicines compendium (EMC) and the chemical database of bioactive molecules with drug-like properties, European Molecular Biology Laboratory (ChEMBL). Results Excluding congenital, familial, and genetic disorders, and endocrine disorders, all other SOCs (n = 5) showed statistical significance (P < .05) for ADRs/1,000,000 items identified across the 13 fluorinated drugs. It was identified that leflunomide was suspected of more ADRs than other comparator medications, which had the highest suspected ADRs/1,000,000 items dispensed (n = 343) and lansoprazole had the lowest (n = 14). Both drugs contain same number of fluorine atoms (n = 3) and similar type of fluorine moiety (trifluoromethyl, -CF3). Conclusion No correlation between the fluorination status of the drugs and the ADRs were found.